Pernikahan Childfree Perspektif Imam Al-Ghazali Dalam Kitab Ihya’ Ulumuddin - Nawawi, Ghufron; Miftahuddin , Abdul Hafidz (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2023)
Marriage is not merely a contractual agreement but holds intrinsic religious value. Therefore, entering into a marital union is an honorable path ordained by Allah to fulfill biological needs as a divine blessing. One of the objectives of marriage is to preserve the biological relationship between man and woman, aimed at nurturing a sacred lineage. However, societal advancements and changing mindsets, particularly in countries like France, England, and the Netherlands, have led some individuals to perceive having children as an additional burden. Consequently, certain families choose not to have children, whether biological, adopted, or stepchildren, a lifestyle commonly referred to as "childfree." The term "childfree" comprises two words: "child," referring to offspring, and "free," signifying freedom. Childfree is a personal choice to abstain from having children, whether before or after marriage, encompassing biological, adopted, or stepchildren. When analyzing childfree marriages through the lens of the book "Ihya’ Ulumuddin," they can be categorized into two types: permissible and impermissible childfree. Permissible childfree marriages include those where contraception methods such as 'azl (coitus interruptus) are employed or when the decision is based on personal reasons such as concerns about the challenges of raising many children and financial considerations. On the other hand, impermissible childfree marriages involve psychological or medical reasons and environmental considerations.